4차 산업혁명시대의 영어교사 미래준비도 연구 - 김형순; Kim Hyoung Soon; 김혜영; Kim Heyong (Multimedia-Assisted Language Learning, 2017)
The purpose of this study is to investigate English teachers’ preparedness in terms of knowledge, attitudes, and perceptions about the upcoming future, namely, the fourth industrial revolution era. To create a questionnaire form, this study defines English teachers’ future readiness in the following categories; 1) technology knowledge and concerns, 2) innovation resistance and anxiety, 3) perceptions toward a new technology impact on English education. The analysis of the survey data yielded the following findings. First of all, teachers’ concern about the impact of new technology on English education was high, but their concern level seemed ‘personal’ (1-2 stages), as well as unrelated to their teaching. In addition, they were comparatively less interested in building knowledge about new technologies. Second, the teachers’ innovation resistance and anxiety were not high. The teachers showed willingness to take new technologies as instructional tools and positive attitude toward technology-embedded future classroom. Third, notwithstanding, they did not believe that new technology would change the existing language education paradigm and solve the problems inside. Younger teachers showed significantly higher skepticism on the future changes.